Correlations Between Domestic Hot Water Consumption and Changes in Outdoor Temperature - Horkai, András (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Residential–household energy consumption accounts for almost one-third of total energy consumption in Hungary. The second-largest factor in household energy costs in most European countries is domestic hot water (DHW) production. According to several studies, DHW consumption is influenced by the physical environment and climatic conditions, including changes in climatic conditions in the long run. The present study demonstrates how DHW consumption is affected by changes in outdoor temperature through the example of a housing estate built with prefabricated (panel) technology in Hungary, Budapest. The model estimating the DHW consumption constructed by regression analysis explains 74% of the values (R2 = 0.7415). The independent variable of the model is the outdoor temperature. The modeling data source was the National Meteorological Service and the district heating provider supplying the housing estate. The study also presents the DHW consumption changes expected to cause climate change, based on the data from one projection of two regional climate models, the ALADIN-Climate and the RegCM model. The developed model and the projections'results can contribute to sustainable resource management and help plan the domestic hot water supply operation.